“Perspective”, Final Project Exhibition Female Artists From Undikma Fine Arts - Mahroni G, Lalu Aswandi; Rahmat, Mi’rajussubyan (Jurnal Ilmiah Mandala Education (JIME), 2025)
Exhibition "Perspective"is a form of presentation of the final assignments of three students of the D3 Fine Arts Study Program, Mandalika University of Education, which displays artistic exploration through the medium of painting and graphic arts. This research aims to examine the concepts, visual approaches, and thematic content in the works of each artist, namely: (1) Fitria Galbi with the theme“The Untranslatable”which raises the muqatta'ah letters from the Qur'an in a contemporary calligraphy format; (2) Inceli Zubaidah with graphic works on the theme"Could be insecure"which expresses personal emotional experiences through visual symbolism; and (3) Nirmala Insani with realistic paintings on the theme“Traditional Equipment of Lombok”as a form of preservation of local cultural objects.The research employed a descriptive qualitative method with a case study approach. Data were obtained through direct observation of the works, interviews with the artists, and the study of relevant literature, including aesthetic theory, Islamic calligraphy, art psychology, and material culture. The analysis revealed that each work reflects a strong, reflective, and contextual creative process within the artists' respective identities, spirituality, and cultural contexts.This exhibition emphasizes the important role of art education as a space for exploration and self-expression, where students not only create works, but also form visual understandings that are relevant to contemporary issues and local values.